CITRA REMAJA DALAM NASKAH DRAMA MAJALAH DINDING KARYA BAKTI SOEMANTO - Farid Ibnu Wahid (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Youth as a milestone of a nation would have to be more alert and ready in changing times. The existence of a teenager is cikalbakal sustainability of a nation continue to exist. Strength teen in the face of competition will raise the dignity of the nation. Teenage is a time of issue. In this paper will discuss the Majalah Dinding at Bakti Soemanto. Majalah Dinding are very interesting to study this is due to the script set in the lives of adolescents in schools that have a conflict with the Principal. Attitudes conducted by Anton Cs reflects adolescent psychiatric always wanted to gain recognition, proper appreciation of friends, parents, and teachers where they are studying. Thus, the authors will try to photograph the mind and the anxiety that occurs in adolescents role in the Majalah Dinding Consecrated charactered terms. This will make it easier to scan the thoughts of each character contained.